(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
There is a long lasting debate between legal scholars if investor state arbitration is part of EU’s judicial system. Some argue that Investor state arbitration is incompatible with the autonomy of EU law and with the role of the Court of Justice of the European Union, which is guarding the uniform interpretation and application of EU law. Some have contrary opinion. In recent decision in Case C-284/16 the Court of Justice of the European Union declared that the investor-state arbitration provision in the bilateral investment treaty between The Netherlands and Slovakia is incompatible with EU law. The Court of Justice of the European Union did not follow the Advocate General’s Opinion, which reached the opposite conclusion. Taking into consideration two opposing opinions, the goal of the paper is to analyse recent case law and argue whether other investment arbitration tribunals set up under intra-EU bilateral investment treaties should be seen as courts common to the member states and are therefore fully part of the EU’s judicial system. The author concludes that as the Court of Justice of the European Union focused only on the specific bilateral investment treaty between the Netherlands and Republic of Slovakia at issue, it is difficult to apply the same argumentation on disputes currently pending under the Energy Charter Treaty if only two member states of the EU are involved.